2009
DOI: 10.1194/jlr.m800625-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids suppress adipocyte lipolysis via activation of the nicotinic acid receptor GPR109A (HM74a/PUMA-G)

Abstract: Phenolic acids are found in abundance throughout the plant kingdom. Consumption of wine or other rich sources of phenolic acids, such as the "Mediterranean diet," has been associated with a lower risk of cardiovascular disease. The underlying mechanism(s), however, has remained unclear. Here, we show that many phenolic acids, including those from the hydroxybenzoic and hydroxycinnamic acid classes, can bind and activate GPR109A (HM74a/PUMA-G), the receptor for the antidyslipidemic agent nicotinic acid. In keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
(35 reference statements)
0
23
1
Order By: Relevance
“…In addition to the direct radical scavenging activity8384, simple phenolic acids, such as ferulic acid, caffeic acid, gallic acid, and cinnamic acid, possess antidiabetic properties85. Consumption of products rich in phenolic acids correlates with a reduced risk of CVD86. Thus, the health-promoting effects of WG wheat consumption observed in epidemiological studies may be attributed in part to the unique phytochemical contents of ARs, BXs, and phenolic acids in this whole grain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct radical scavenging activity8384, simple phenolic acids, such as ferulic acid, caffeic acid, gallic acid, and cinnamic acid, possess antidiabetic properties85. Consumption of products rich in phenolic acids correlates with a reduced risk of CVD86. Thus, the health-promoting effects of WG wheat consumption observed in epidemiological studies may be attributed in part to the unique phytochemical contents of ARs, BXs, and phenolic acids in this whole grain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high (Ͼ95%) homology between the two receptors, nicotinic acid is in fact very selective for the HCA 2 receptor. Acifran, however, is not very selective for the two receptors, with slightly lower micromolar affinity for the HCA 3 receptor (for example, Mahboubi et al, 2006;Ren et al, 2009). The most extensive structure-activity study with acifran analogs showed that an ethyl rather than a methyl substituent at the chiral center in acifran (see Fig.…”
Section: B Structure-activity Relationships For the Hca 3 Receptormentioning
confidence: 95%
“…3 H]nicotinic acid radioligand displacement assay, somewhat lower K i values were obtained: for MMF, 0.98 M; for MEF, 1.3 M. A number of "simple" acids were tested by Ren et al (2009) (Fig. 8) can be regarded as derivatives of nicotinamide (Fig.…”
Section: Fumaric and Other Acids And Their Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…In adipocytes, energy availability is communicated indirectly through insulin concentrations and sympathetic tone (4) but is also sensed directly through G protein-coupled receptors. In adipose tissue, G protein-coupled receptors respond to short chain fatty acids, lactate, ␤-hydroxybutyrate, ␤-hydroxyoctanoate, and succinate to mediate effects on lipolysis (5)(6)(7)(8)(9). A hypothesis explored in this study is whether nutritive signals regulating adipocyte differentiation and metabolism are also mediated in part by sweet taste receptors.…”
mentioning
confidence: 99%